Preview of highlighted presentations from the European Respiratory Society’ clinical assembly - Kahn, Nicolas; Vanfleteren, Lowie E. G. W.; Kaltsakas, Georgios; Andrianopoulos, Vasileios; Gompelmann, Daniela; de Jong, Corina; Herth, Felix J. F. (Journal of Thoracic Disease; Vol 10, Supplement 25 (September 2018): Journal of Thoracic Disease [Dedicated to the 28th International Congress of the European Respiratory Society (ERS 2018)], 2018)
This paper highlights a selection of abstracts that will be presented at the 2018 European Respiratory Society (ERS) International Congress in Paris. The abstract were submitted through the five different groups of our society largest assembly, the clinical assembly (assembly 1).